THE INFLUENCE OF PROFITABILITY RATIOS, CAPITAL STRUCTURE AND SHAREHOLDING STRUCTURE AGAINST ON VALUE COMPANY (EMPIRICAL STUDY OF COAL MINING COMPANIES LISTED ON THE STOCK EXCHANGE OF INDONESIA YEAR 2011-2013) - Gilang Ramadhan Fajri; Dwi Asih Surjandari (The Accounting Journal of Binaniaga, 2016)
This study has the objective to assess the "Influence of Profitability Ratios, Capital Structure and Shareholding Structure Against On Value Company (Empirical Study of Coal Mining Companies Listed on the Stock Exchange of Indonesia Year 2011-2013)" The analysis technique used in this research is multiple linear regression and hypothesis testing using tstatistic to test the partial regression coefficient and f-statistic to test the feasibility of the research model with a 10% level of significance. It also conducted a classic assumption test including normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. Based on the results of the study indicate that Profitability Return on equity positive effect on firm value. Earning pershare significant positive effect on the value of the company. The capital structure has a positive effect on firm value. institutional ownership has significant negative effect on the value of the company. Managerial ownership negatively affect the value of the company.Keywords: Profitability Ratios, Institutional Ownership, Managerial Ownership, Capital Structure, Corporate Values.